Understanding the European Union's regional potential in low-carbon technologies - Enrico Bergamini; Georg Zachmann (Bruegel, 2020)
Our research identifies existing and potential specialisation in green technologies in European Union regions, and proposes an approach to identify policies that can help to realise this potential. Using the Organisation for Economic Cooperation and Development's REGPAT database for regionalised patent data, we estimate the potential advantage European NUTS2 regions could have in 14 green technologies. We use network proximity between technologies and between regions to understand technological/regional clusters, and build the regressors for estimating potential regional advantage in specific technologies via zero-inflated beta regressions. We construct a dataset of lagged potentials and labour market, economic and demographic variables, and perform an elastic net regularisation to understand the association with current revealed advantages. Our approach indicates an association between technological advantage in green technologies in EU regions and participation rates in labour markets, sectoral employment in science and technology, general higher education, duration of employment, percentage of GDP spent on research and development (public and private), and other expenditure on R&D. If confirmed by causality tests, the established associations could help in designing horizontal economic policies to enable specific regions to realise their specialisation potential in specific green technologies.
Keywords: 330